The informational role of prestigious gatekeepers under different economic conditions and regulatory reforms: the case of the IPO market - Attuwaijri, Hend (2020)
Underwriters, industry specialist auditors, and credit rating agencies release valuable information about corporations’ value to the capital markets. Under the information asymmetry hypothesis, underwriters, industry-specialist auditors and credit rating agencies boost firm transparency and, hence, decrease the extent of informational asymmetries. Previous studies present evidence that managers tend to manipulate earnings around IPOs. If managers opportunistically manipulate earnings in the IPO year, the reported earnings will not be sustainable, and the IPO firms will exhibit negative abnormal stock returns in subsequent periods due to investors’ downward adjustment of their evaluation of the firm’s value. Therefore, in this thesis I aim to explore the potential effect of the presence of prestigious gatekeepers, namely the multiple lead underwriters (MLUs), industry specialist auditor (jointly city-national level) and, finally, credit rating on the level of earnings management around IPO and the managers’ choices of accrual-based and real earnings management. I employ the entire US common share IPO for the period from 2000-2014, and the results show that MLUs restrict accrual-based and real earnings management in terms of cashflow from operation (CFO). Consequently, firms have resorted to discretionary expenses manipulation. Meanwhile, industry-specialist auditors tend to restrict all forms of accruals-based and real earnings management. For credit rating I observe a negative and significant relation between the presence of rating and accrual-based and sales-based manipulations, this, in turn, results clients engaging in a higher level of production-based earnings management.